المحاكمة العادلة في الإسلام من خلال رسالة عمر بن الخطّاب إلى أبي موسى الأشعري (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The Justice Is The Cornerstone Of Governance And Power, Hence, Islam Has Given More Importance To Implementing Justice And Putting Certain Conditions For The Judges About How To Conduct Trials In The Court And Honoured Them As The Highest After The Prophet Mohammed, The Messenger Of Allah, Peace Be Upon Him,  Abu Bakr Al Sidique And Omar Bin Khattab, May Allah Be Pleased With Him; Who Contributed Enormously With His Advice And Guidance To The Judges And Governors On How To Conduct Fair Trials; Perhaps The Most Important Of This Directives Is The One That He Sent To Abu Musa Al- Ash’ari Providing Him With The Judicial Steps Which Became Judicial Clauses For The Fair Trial. Key Words-The Judiciary Document/ Justice/ Fair Trial/   Message Omar Bin Khatab.